2001
DOI: 10.1017/s0003598x00060981
|View full text |Cite
|
Sign up to set email alerts
|

Absolute age range of the Late Cypriot IIC Period on Cyprus

Abstract: Extensive radiocarbon data are examined, including results from short-lived samples contemporary with use-contexts. An absolute date range for the main Late Cypriot IIC period on Cyprus, from c. 1340–1315 BC to c. 1200 BC, is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…The LBA crisis, associated with a wave of destructions led by a flow of migrants, the Sea Peoples, is clearly attested in Cyprus with the end of the Late Cypriot IIC period, and the Late Cypriot IIC-IIIA transition dated to 1220–1190 cal yr BC [76]–[77]. Late Cypriot IIC ceramics, imported from Cyprus, were also found at Gibala-Tell Tweini (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The LBA crisis, associated with a wave of destructions led by a flow of migrants, the Sea Peoples, is clearly attested in Cyprus with the end of the Late Cypriot IIC period, and the Late Cypriot IIC-IIIA transition dated to 1220–1190 cal yr BC [76]–[77]. Late Cypriot IIC ceramics, imported from Cyprus, were also found at Gibala-Tell Tweini (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This resulted in an "old wood" bias of greater magnitude than the difference between the 2 models. While the material from Cyprus (Manning et al 2001) is of more value in that it contains a significant number of short-lived examples, the error range was still too large to clearly distinguish between the Conventional and Ultra-low models. A further contributing factor in the case of the Cypriot data involves the uncertainty of the timing of the destruction or abandonment of various Cypriot centers near the end of the LC IIC period.…”
Section: Discussionmentioning
confidence: 99%
“…Although this proposal was severely critiqued 1 and has not subsequently been accepted, one of the more severe opponents did concede that the absolute dates of the New Kingdom depend not on Sothic dating but on records of king-lists and synchronisms with historical data in Syro-Palestine and western Asia (Kitchen 1991:237). The critical reaction to James et al included 2 reviews of radiometric data by Manning and Weninger (1992) and Manning et al (2001) in which the authors concluded that the Conventional chronology was "approximately correct" and that their work had brought an end to "radically lower LBA chronologies in the eastern Mediterranean and Near East" (Manning et al 2001:340). Since then, the conventional Egyptian chronology has been generally retained, with the Low version of the allowed astronomical range increasingly preferred (Wente and Van Siclen 1976).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we employ the relative dating of the Late Cypriote (LC) period according to the basic tripartite system (LC I, LC II, and LC III) developed by Gjerstad (1926: 262-289), which was further refined and linked to absolute dating by, for example, the Swedish Cyprus Expedition (SCE IV: ID) and Merrillees (1977Merrillees ( , 1992 based on comparisons with chronologies from Egypt, the Near East, and the Aegean. Additional radiocarbon dating is provided by Manning et al (2001) and adapted by Hadjisavvas (2007), and our dating is based on these studies. The approximate dates for the LC period are as follows: LC IA c. 1650-1550, LC IB c. 1550-1450, LC IIA c. 1450-1375, LC IIB c. 1375-1340/1315, LC IIC c. 1340/1315-1200, LC IIIA c. 1200-1125(Merrillees, 1992Manning et al, 2001;Hadjisavvas, 2007).…”
Section: Archaeological Contexts and Pottery Samples Pottery Sherds Omentioning
confidence: 99%